Detection and Occurrence of Microcystins and Nodularins in Lake Manatee and Lake Washington-Two Floridian Drinking Water Systems - Melaram, Rajesh; Lopez-Dueñas, Brandon (Frontiers in Water, 2022)
Clean, fresh, and safe drinking water is essential to human health and well-being. Occasionally, biological contaminants taint surface water quality used for human consumption and recreation. Microcystins (MCs) and nodularins (NODs) are toxic monocyclic peptides produced by cyanobacteria in fresh and brackish water. These secondary metabolites can reach hazardous concentrations, impairing surface drinking water supplies and thereby increasing the risk of exposure to consumers. Inconsistent screening of MCs and NODs is not uncommon in drinking water systems and no provisional guidance value has been established in Florida to protect community and public health. We performed a case study of two Florida lakes supplying drinking water to adjacent communities for the purpose of monitoring MCs and NODs over the potential peak algae bloom season (June-August). An indirect competitive enzyme-linked immunosorbent assay (icELISA) was employed to analyze concentrations of total MCs and NODs in environmental water samples from Lake Manatee and Lake Washington. Toxin concentrations were similar in each lake, averaging 0.19 µg/L. The highest toxin concentration (0.46 µg/L) was reported in Lake Manatee at Site 15, a location where other toxin concentrations demonstrated statistical significance with toxins detected at Sites 6 (p = 0.014) and 8 (p = 0.011). Inferential analyses from the Kruskal-Wallis H Test revealed a statistically significance difference in toxin concentrations by sampling month within the two Floridian drinking water systems (p < 0.001). Furthermore, phosphate and nitrite concentrations strongly correlated with total MCs and NODs in each lake (p < 0.01). Although results indicate a low probable health risk from cyanotoxins, more research is needed to understand the intrinsic nature of MCs and NODs by examining their prevalence, distribution, and dynamics in surface drinking water supplies serving nearby communities.